Ionospheric response to tidal waves measured by dynasonde techniques. Issue 1 (16th January 2016) - Negrea, Cătălin; Zabotin, Nikolay; Bullett, Terence; Codrescu, Mihail; Fuller‐Rowell, Tim
Abstract: Atmospheric tides are known to have a dramatic influence on thermospheric and ionospheric structure and variability. Considerable effort goes into understanding characteristics of tidal modes, their interactions with planetary and gravity waves and other tidal modes, as well as their influence on the background state of the thermosphere‐ionosphere system. For the altitude interval between roughly 120 and 400 km, this effort is somewhat hindered by the lack of global observations. We propose a new method of determining tidal variability by making use of dynasonde measurements. The NeXtYZ inversion procedure produces altitude profiles of the ionospheric parameters with a vertical resolution typically better than 1 km. This, together with the typical 2 min cadence of the instrument, results in extensive data sets with wide temporal and altitude coverage. At any given altitude we have nonuniform sampling due to the natural ionospheric variability. A Lomb‐Scargle implementation is used to obtain equivalent results at all altitudes and locations. We report height profiles of the first three tidal harmonics derived from dynasonde measurements. The data analyzed include the vertical electron density profiles, the ionospheric X (east‐west) "tilt" measurement, and the derived zonal plasma density gradient. Both the tilt and the gradient are shown to be sensitive tracers of atmospheric waves. We use data from Wallops Island and San Juan, for two time intervals: 6 May‐ 6 June and 9 October‐ 8 November 2013, thus capturing seasonal, latitudinal, and altitude variations of tidal amplitude and phase. This proves the potential of using dynasonde‐capable instruments as a data source for tidal studies in the thermosphere. Key Points: Dynasonde data are used to determine the magnitude and phase of tidal harmonics Variability of the first three tidal harmonics between 140 and 300 km altitude Existence of several distinct altitude ranges showing higher tidal amplitudes